Does It Matter Where They Train?: Transitions into Higher Education After VET and the Role of Labour Market Segments - Grønning, Miriam (Social Inclusion, 2019)
Due to a higher demand for tertiary education, continued educational achievement has become important for the career development of young people with vocational education and training (VET). In this article, therefore, we examine whether the labour market segment of the training firm influences VET diploma holders’ likelihood of entering tertiary education. In Switzerland, companies from a wide range of industries and with different institutional characteristics assume a large part of the responsibility for training. Thus, the training firm’s position in the labour market impacts apprentices’ education and training. Drawing upon segmentation theories, we argue that structural differences between training firms in different labour market segments result in varying opportunities and incentives for higher education. Our analyses are based on a longitudinal national survey of healthcare apprentices who were trained in the primary healthcare segment (hospitals) or in the secondary healthcare segment (nursing homes). Propensity score matching results show that VET diploma holders who were trained in the primary segment were more likely to enter tertiary education than those who were trained in the secondary segment. This finding implies that the structural conditions in the training firm matter for young workers’ careers by affecting further educational achievement.